Postoperative femoral head cartilage injury after hip arthroscopic treatment for femoroacetabular impingement syndrome and labral tear - Guanying Gao; Yichuan Zhu; Siqi Zhang; Yingfang Ao; Jianquan Wang; Yan Xu (Journal of Orthopaedics and Traumatology)
Abstract Background Postoperative femoral head cartilage injury (FHCI) is a rare condition that can be observed in a certain proportion of patients undergoing hip arthroscopy. However, the prevalence and associated factors of FHCI, and the effect of this condition on clinical outcomes still remain unknown. Patients and methods Consecutive patients who were diagnosed with femoroacetabular impingement syndrome (FAIS) and labral tear and underwent hip arthroscopic treatment in our institute between July 2020 and July 2021 were retrospectively evaluated. Supine anteroposterior hip radiographs, cross-table lateral radiographs, magnetic resonance imaging (MRI), and computed tomography (CT) were obtained preoperatively. Postoperative MRI, at least 6 months after arthroscopy, was performed. Postoperative FHCI was evaluated by two surgeons through MRI. Preoperative patient-reported outcomes (PROs) including visual analog scale (VAS) for pain, and modified Harris Hip Score (mHHS) before surgery and at final followup were obtained. Results A total of 196 patients were included. Postoperative FHCI was identified in 21 (10.7%) patients. The intraobserver reliability of the observer A and B for detecting postoperative FHCI using 3.0-T MRI was high (k = 0.929, and k = 0.947, respectively). The interobserver reliability between the two observers for detecting FHCI using 3.0-T MRI was high (k = 0.919). There was no significant difference in preoperative and postoperative mHHS, VAS, and percentage of patients who surpassed minimal clinically important difference (MCID) and achieved patient acceptable symptom state (PASS) between patients with and without postoperative FHCI (P > 0.05). Conclusion Although postoperative FHCI was observed in 10.7% of patients, which was associated with larger labrum, this condition did not result in inferior clinical outcomes. Level of evidence IV, retrospective case series. Trial registration The Chinese Clinical Trial Registry approved the registration (ChiCTR2200061166). The date of registration is 2022-06-15.